2023
DOI: 10.3390/en16072973
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carbonate Formation during CO2 Hydrogenation over MgO-Supported Catalysts: A Review on Methane and Methanol Synthesis

Abstract: Methane and methanol are promising products for CO2 hydrogenation for carbon capture and utilization concepts. In the search for effective, robust, easy-to-manufacture and stable catalysts, supported metal-based catalysts have proven advantageous. Whereas nickel for methane synthesis and copper for methanol synthesis stand out as efficient and cost-effective catalytically active metals, the best choice of support material is still a matter of ongoing debate. This review discusses the potential of the alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…The notable advantage of this synthetic approach lies in achieving phase purity even at exceptionally high substitution levels, such as x = 0.5, which exceeds the critical limit observed with conventional coprecipitation methods. Unlike Cu/ZnO, the literature is scarce concerning the optimizations in the chemistry of Cu/MgO binary catalysts involving both synthesis and catalytic performance toward methanol. ,, The presence of MgO has been observed to boost surface basicity, increase defect site concentration, and aid in the dispersion of Cu 0 , thereby influencing both the overall activity and selectivity to methanol formation. Moreover, some reports suggest that MgO inhibits the reverse water gas shift reaction (rWGS) while facilitating CO 2 activation at lower temperatures to produce methanol through CO 2 hydrogenation. , Schumann et al also observed that adding MgO lowers the conductivity and reducibility of ZnO, affecting the interaction between the catalyst and support in rWGS and methanol synthesis reactions . Computational findings by CaO et al identified the MgO–Cu interface as a highly active surface and proposed a unique mechanism involving lattice oxygen at the interface aiding methanol formation.…”
Section: Introductionmentioning
confidence: 99%
“…The notable advantage of this synthetic approach lies in achieving phase purity even at exceptionally high substitution levels, such as x = 0.5, which exceeds the critical limit observed with conventional coprecipitation methods. Unlike Cu/ZnO, the literature is scarce concerning the optimizations in the chemistry of Cu/MgO binary catalysts involving both synthesis and catalytic performance toward methanol. ,, The presence of MgO has been observed to boost surface basicity, increase defect site concentration, and aid in the dispersion of Cu 0 , thereby influencing both the overall activity and selectivity to methanol formation. Moreover, some reports suggest that MgO inhibits the reverse water gas shift reaction (rWGS) while facilitating CO 2 activation at lower temperatures to produce methanol through CO 2 hydrogenation. , Schumann et al also observed that adding MgO lowers the conductivity and reducibility of ZnO, affecting the interaction between the catalyst and support in rWGS and methanol synthesis reactions . Computational findings by CaO et al identified the MgO–Cu interface as a highly active surface and proposed a unique mechanism involving lattice oxygen at the interface aiding methanol formation.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that some researchers have suggested that the presence of carbonate is not favorable for CO2 activation and hydrocarbon formation using Fe-based catalysts [23]. This is because carbonate can compete with CO2 for adsorption sites on the catalyst surface, thereby reducing the amount of CO2 available for reaction.…”
mentioning
confidence: 99%